IMPLEMENTATION OF CHILD-FRIENDLY SCHOOLS IN DEVELOPING STUDENTS’ CHARACTER - Ikka Kartika Abbas Fauzi; Nana Mulyana; Iis Farida Zein (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses how far the implementation of child-friendly schools is in developing the character of students at SDN Dewi Sartika CBM by using a qualitative descriptive research method. The research begins with interviews and questionnaires. The research was conducted by analyzing the stages of planning, organizing, implementing, supervising, and developing strategies. The planning indicators are to carry out a study of the 8 SNP and create a child-friendly school implementation program. The implementation indicators are to create a program implementation team and divide the tasks of the program implementation team. The implementation indicators are to launch a child-friendly school program, make a joint commitment to friendly school implementation, and prepare childfriendly infrastructure, implement child-friendly schools into the 8 SNP (National Education Standards), and determine achievement targets for the 8 SNP. Monitoring indicators are tomonitor the results of observing program implementation and follow-up plans. The implementation of child-friendly schools in developing students’ character indicates positive results in order to prepare schools that are ideal, safe, and comfortable for learning activities, by implementing them properly as well as has been implemented at SDN Dewi Sartika CBM. According to the results of research on the implementation of child-friendly schools at Dewi Sartika CBM Elementary School, it runs well based on the program plan with an average achievement of 87.50% in the good criteria.